Bridging Borders Central Asian Cross-Border Cooperation in a Comparative Global Perspective - Golunov, Sergei; Bitabar, Assel; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
The open access book analyzes cross-border cooperation (CBC) in Central Asia from a comparative perspective. It provides new insights into four main areas: (1) It highlights international experiences in CBC to identify best practices for Central Asian states; (2) it discusses various policies of Central Asian states towards CBC, specifically those policies that impact Central Asian CBC either positively or negatively; (3) it identifies best practices and actors for successful CBC in Central Asia, including the role of non-governmental entities; (4) it provides recommendations for enhancing Central Asian CBC, drawing upon both international experiences and a thorough analysis of Central Asian contexts. The authors proceed from the assumption that effective cross-border cooperation is one of the essential conditions for successful regional integration, as it acts as a connective seam between participating states. Unfortunately, at present, no Central Asian country excels in CBC; in every case, CBC is impeded by highly centralized political systems, and lack of funding. To enhance CBC in Central Asia, it is crucial to examine the relevant experiences of other countries and regions, incorporating lessons from both successful and unsuccessful endeavors.
Chapter 1. Introduction -- Chapter 2. Overview of Global Cross-Border Cooperation Experience -- Chapter 3. Central Asian Cross-Border Cooperation -- Chapter 4. Adapting Global Cross-Border Cooperation Experiences for Central Asia.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Asia -- Politics and government; Regionalism; Security, International; Asian Politics; Regionalism; International Security Studies